Increase of glial fibrillary acidic protein and S-100B in hippocampus and cortex of diabetic rats: effects of vitamin E - Baydas, G; Nedzvetskii, VS; Tuzcu, M; Yasar, A; Kirichenko, SV (Elsevier Science Bv, 2003)
Glial interactions with neurones play vital roles during the ontogeny of the nervous system and in the adult brain. Physical and metabolic insults cause rapid changes in the glial cells and this phenomenon is called reactive gliosis. One of the important events during astrocyte differentiation is the increased expression of glial markers, glial fibrillary acidic protein (GFAP) and S-100B protein. Diabetes mellitus is the most common serious metabolic disorder, which is characterised by functional and structural changes in the peripheral as well as in the central nervous system. In the present study, we aimed to investigate glial reactivity in hippocampus, cortex and cerebellum of streptozotocin-induced diabetic rats by determining the expression of GFAP and S-100B and also to examine the protective effects of vitamin E against gliosis. Western blotting showed increases in total and degraded GFAP content and S-100B protein expression in brain tissues of diabetic rats compared with those of controls. In addition, there was a significant increase in lipid peroxidation in these brain regions of diabetic rats. Both glial markers and lipid peroxidation levels were reversed by vitamin E administration. these findings, indicate that streptozotocin-induced diabetes alters degradation and production of GFAP and S-100B, which are markers of reactive astrocytosis. Thus, determination of GFAP and S-100B may provide a relevant marker in the central nervous system for studying neurodegenerative changes in experimental diabetes mellitus. This study also suggests that the gliosis that occurs in diabetes mellitus is mediated, at least indirectly, by free radical formation and antioxidants may prevent reactive gliosis possibly by reducing damaging effects of reactive oxygen species in the central nervous system. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: diabetes; streptozotocin; lipid peroxidation; hippocampus; cortex; GFAP (glial fibrillary acidic protein)